The Effects of Different Environmental Conditions on the Characteristics of Fiber Reinforced Plates - Ghydaa K. Yass; Safaa H. Abdul Rahman (Engineering and Technology Journal, 2010)
The failure of polymer matrix composite upon exposure to the environmentconditions has been assessed in the present study. Glass fabrics and unsaturatedpolyester resin were selected to fabricate 8-layer laminates cross ply [(0/90)8]arranged in symmetric and antisymmetric stacking sequence. Environmentalconditioning using Sea and Tap water with humidity exposure and Ultravioletradiation was conducted to investigate the vibrations characteristics of symmetricand antisymmetric composite samples. After exposure time to the conditionsabove for 500, 1000 and 2000 hr, laminates were subjected to three point bendingtesting, in order to study their flexural properties (stiffness and strength) beforeand after these exposures. Then a finite element analysis using the packageprogram ANSYS (version 10) was used for the analysis of free vibrationcharacteristics. The object was to obtain the natural frequency for each case ofenvironmental conditions at different exposure times. The results showed thatnatural frequencies of cantilever laminate plates decreased with the increasedexposure time for the different environmental conditions.